Modelling of integral hinges via CadMould 3d-F injection moulding simulation - Othman, M.H.; Osman, S.A.; Amin, S.Y.M.; Rosli, M.S. (Elsevier, 2018)
This project was conducted to define the suitable model of runner size and gate location of the integral hinges samples, via CadMould 3D-F simulation. This simulation was used to analyse the effects of mould design towards the quality and injection moulding processing output of thermoplastics integral hinges test samples. Runner size and gate location were chosen for design parameter. The result shows that the mould design 2 with larger runner size (Test 1) has lowest temperature when filled, which is 240.1°C and lowest completely time filled (0.147 seconds). It also have lowest value of volume shrinkage (0.564%) and second lowest warpage (0.025 mm).As for the conclusion, the findings this project could be a reference for the mould makers for products consisting of integral hinge or tension band region. Moreover, good mould produces better samples, therefore the effect of mould design towards samples’ quality could be controlled and confined.